Fieldwork’s Return: Troubled Steps Towards A Multispecies Imaginary - Aisher, Alexander (Material religion, 2020)
For many anthropologists, longterm ethnographic fieldwork does not end when they leave the field, as the journey towards ethnographic understanding evolves for years after physically returning from the field. In an auto-ethnographic mode, this paper traces the author’s return journey from the field, through transformations in their understanding of soul abduction and spirit-revenge among upland members of the Nyishi tribe in the Eastern Himalayas. The paper traces the author’s journey from initial ontological immersion in fieldwork materials, through a reductionist withdrawal from the data, to the “redemptive symmetry” of a multispecies approach: one which recognizes the human and more-than-human origins of such spirit phenomena.